Estrés Laboral y su incidencia socio emocional en los trabajadores del Gad Municipal del cantón Zamora en la actualidad - Cajas Soto, Katherin Gissela (2025)
This research focuses on occupational stress and its socioemotional incidence in workers of the GAD Municipal del Cantón Zamora in the current period. This phenomenon, common in many work environments, can damage the physical and mental health of employees, not only impacts at the professional level, but can also lead to personal and family problems, generating anxiety and affecting the general health of individuals. The methodology used is a mixed approach, combining quantitative and qualitative data to analyze work stress. Surveys are used to collect numerical data measuring objective variables and in-depth interviews to capture the subjective experiences of employees. This mixed approach and the use of various data collection instruments seek to diagnose the incidence of stress and develop effective intervention proposals. The analysis of the results obtained in the study conducted in Gad Municipal del Cantón Zamora, with a population of 37 workers and 10 employees, the instruments applied were focused on analyzing stress and the socioemotional incidence of workers. The study found that work stress has a negative effect on the productivity and performance of employees. Since stress can decrease concentration, increase errors and reduce efficiency. In addition, burnout and mental fatigue can lead to a decrease in employees' ability to perform their responsibilities effectively. This not only affects individuals, but can also have a negative impact on overall organizational performance